2016
DOI: 10.3389/fpsyg.2016.01691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imagined Consumption and Simulated Eating Movements on Food Intake: Thoughts about Food Are Not Always of Advantage

Abstract: Imagined food consumption is a method of elaborately imagining oneself eating a specific food that, when repeated 30 times, has been shown to decrease subsequent intake of the same food. The technique relies on a memory-based habituation process when behavioral and motivational responses to a stimulus decrease after its repeated presentation. Thus, repeatedly imagining food consumption leads to food-specific habituation effects. Large numbers of imagined consumption repetitions are effortful and time consuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…An advantage of this approach is that it can be pursued with minimal effort. In contrast, interventions which attempt to modify (instead of activating elements of) the existing cognitive structures that underlie individuals’ health-related behavior, such as making specific plans for how to behave in response to tempting situations, mostly involve a form of training which is normally time-consuming ( Haasova et al, 2016 ; Papies, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this approach is that it can be pursued with minimal effort. In contrast, interventions which attempt to modify (instead of activating elements of) the existing cognitive structures that underlie individuals’ health-related behavior, such as making specific plans for how to behave in response to tempting situations, mostly involve a form of training which is normally time-consuming ( Haasova et al, 2016 ; Papies, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we proposed that the repetitive use of appetite questionnaires would affect subsequent food intake given that provoking thoughts of food consumption increases food intake (18, 19). The thoughts of food experienced when considering perceived hunger and fullness (part of the cephalic phase) may evoke a cephalic phase response and initiate a cascade of preabsorptive physiological responses to initiate feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research showed that the availability of self-regulatory resources is necessary for the reduction in food intake induced by repeated imagined consumption to occur (see also Missbach et al 2014, Study 2). Haasova et al (2016) asked participants to imagine eating chocolate pudding 15 or three consecutive times. Results showed that participants who imagined eating the chocolate pudding 15 times ate more of the pudding than those who imagined consuming it three times.…”
Section: The Effect Of Hedonic Mental Simulation On Food Choice and Pmentioning
confidence: 99%